Akta Pengangkatan Anak Tanpa Putusan Pengadilan: Keabsahan dan Akibat Hukum Waris - Auliya Khairunnisa Shabira (Fakultas Hukum, Universitas Warmadewa, 2026)
Adoption is an important aspect of family life because it involves the rights and obligations between parents and Adoption plays a significant role in family life as it relates to the fulfillment of rights and obligations between parents and children. Indonesian law requires that the process of child adoption be carried out through a court decree in order to obtain binding legal force. However, in practice, many people still adopt children solely through a notarial deed without seeking court approval. This situation reflects a gap between the applicable legal provisions and the practices that occur within society. This study aims to examine the legal validity of a notarial deed as the basis for child adoption without a court decree and to analyze its legal consequences on the inheritance rights of the adopted child. The research applies a normative juridical method using a statutory approach and literature review. The results indicate that a notarial deed of child adoption made without a court decree does not have binding legal force and therefore cannot establish a civil legal relationship between the adoptive parents and the adopted child, including in matters of inheritance. In such circumstances, the adopted child may only receive a share of the adoptive parents’ assets through grants, wills, or obligatory wills (wasiat wajibah). Accordingly, a court decree is essential to ensure legal certainty and legal protection for the adopted child in the future.